The Topography of the Central and Peripheral Cornea - Read, Scott A; Collins, Michael J; Carney, Leo G; Franklin, Ross J (Investigative ophthalmology & visual science, 2006)
To investigate the topography of the central and peripheral cornea in a group of young adult subjects with a range of normal refractive errors. Corneal topography data were acquired for 100 young adult subjects by a method that allows central and peripheral maps to be combined to produce one large, extended corneal topography map. This computer-based method involves matching the common topographical features in the overlapping maps. Corneal height, axial radius of curvature, and axial power data were analyzed. The corneal height data were also fit with Zernike polynomials. Conic fitting to the corneal height data revealed the average apical radius (Ro) was 7.77 +/- 0.2-mm and asphericity (Q) was -0.19 +/- 0.1 for a 6-mm corneal diameter. The conic fit parameters were both found to change significantly for increasing corneal diameters. For a 10-mm corneal diameter, Ro was 7.72 +/- 0.2 mm and Q was -0.36 +/- 0.1. A slight but significant meridional variation was found in Q, with the steepest principal corneal meridian found to flatten at a slightly greater rate than the flattest meridian. The RMS fit error for the conic section was found to increase markedly for larger corneal diameters. Higher-order polynomial fits were needed to fit the peripheral corneal data adequately. Analysis of the axial power data revealed highly significant changes occurring in the corneal best-fit spherocylinder with increasing distance from the corneal center. The peripheral cornea was found to become significantly flatter and to decrease slightly in its toricity. Individual subjects exhibited a range of different patterns of central and peripheral corneal topography. Several of the higher order corneal surface Zernike coefficients were found to change significantly with increasing corneal diameter. Highly significant changes occur in the shape of the cornea in the periphery. On average, the peripheral cornea becomes significantly flatter and slightly less astigmatic than the central cornea. A conic section is a poor estimator of the peripheral cornea.